1982
DOI: 10.1083/jcb.92.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phagocytosis-associated surface proteins of macrophages by two-dimensional gel electrophoresis.

Abstract: Two-dimensional PAGE (P . Z. O'Farrell, H. M. Goodman, and P . H . O'Farrell . 1977 . Cell . 12 :1133-1142 has been employed to assess the effects of antibody-dependent phagocytosis on the cell surface protein composition of RAW264 macrophages. Unilamellar phospholipid vesicles containing 1% dinitrophenyl-aminocaproyl-phosphatidylethanol amine (DNPcap-PE) were used as the target particle . Macrophages were exposed to anti-DNP antibody alone, vesicles alone, or vesicles in the presence of antibody for 1 h at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Model membranes containing antigens or lipid haptens can participate in both afferent and efferent immune reactions in vitro and in vivo (1)(2)(3)(4)(5)(6)(7)(8)(9). Considerable interest has been focused on the use of liposomes or lipid vesicles as targets of immune effector cell function (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Studies employing T cells (6)(7)(8)(9), neutrophils (10, 1 1), and macrophages (1 1-20) have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model membranes containing antigens or lipid haptens can participate in both afferent and efferent immune reactions in vitro and in vivo (1)(2)(3)(4)(5)(6)(7)(8)(9). Considerable interest has been focused on the use of liposomes or lipid vesicles as targets of immune effector cell function (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Studies employing T cells (6)(7)(8)(9), neutrophils (10, 1 1), and macrophages (1 1-20) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing T cells (6)(7)(8)(9), neutrophils (10, 1 1), and macrophages (1 1-20) have been reported. In particular, recent studies on phagocyte-liposome recognition have explored the kinetics of internalization (12), respiratory burst (11), cell surface receptor activity (13), membrane protein composition (14), and surface morphology (16). Moreover, modifications of lipid (17), glycolipid (18), and carbohydrate (19) composition have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies characterized the enzyme content of phagocytic vacuoles, examined transport functions of the neutrophil plasma membrane after phagocytosis, and demonstrated that plasma membrane constituents are incorporated into the phagosomes (9,20,50,51,54,57,58). Experiments with surface labeled polymorphonuclear leukocytes (PMN) ~ and macrophages have demonstrated losses in plasma membrane constituents during phagocytosis (20,50,57,58) and, in several cases, the appearance of these molecules in the phago- cytic compartment has been documented. In at least one instance, differential loss of functional surface receptor activity for the Fc portion of IgG (Fc receptor) with no loss of functional surface C3b receptor activity was suggested during phagocytosis of an antibody-coated particle by macrophages (39).…”
mentioning
confidence: 99%
“…Earlier studies characterized the enzyme content of phagocytic vacuoles, examined transport functions of the neutrophil plasma membrane after phagocytosis, and demonstrated that plasma membrane constituents are incorporated into the phagosomes (9,20,50,51,54,57,58). Experiments with surface labeled polymorphonuclear leukocytes (PMN) ~ and macrophages have demonstrated losses in plasma membrane constituents during phagocytosis (20,50,57,58) and, in several cases, the appearance of these molecules in the phago-K. Joiner's present address, where reprint requests should be sent, is Division of Infectious Disease, P. O. Box 3333, Yale University School of Medicine, New Haven, CT 06510.…”
mentioning
confidence: 99%
“…Virtually all of these concerned liposomes specifically designed to trigger fusion upon acidification of the medium (CONNOR et al 1984;STRAUBINGER et al 1985;ELLENS et al 1985;NAYAR and SCHROIT 1985). This has been most thoroughly established for phagocytic cells such as macrophages (MUNN and PARCE 1982;MEHTA et al 1982;RAZ et al 1981;HAFEMAN et al 1980;HOWARD et al 1982;DUKSTRA et al 1984aDUKSTRA et al ,b, 1985a, but also for several non-phagocytic cells endocytosis has been described as the major if not only mechanism of liposome uptake (POSTE and PAPAHADJOPOULOS 1976;FRALEY et al 1980FRALEY et al , 1981. Extracellular conditions of sufficiently low pH are very unlikely to be met in the in vivo situation and will probably be restricted to in vitro conditions where liposomes may be made to fuse directly with the plasma membrane.…”
Section: Interactions With Cellsmentioning
confidence: 99%